A teoria das inteligências múltiplas como contribuição para superação do fracasso escolar - Golin, Alice Felisbino (2003)
For believing that the scholarly education exerts an important paper in the person's life and that ones that fail in the school are precociously dispossess of the basic right to learn, this dissertation proposed it to analyze the school failure and its possible overcoming through the Theory of Multiple Intelligences. The present research characterized as a study predominantly descriptive and exploratory searched through the case study to know the view of the repeating students, as well as, the teacher’s attitudes and positions in front of the school failure. The main intention of the datum collection was to try to trace a perspective of the education on the theory of the multiple intelligences being acted mainly on the teacher’s unilateral position. To show ways to overcome the school failure, through the use of the theoretical approach of the multiple intelligences, finished for becoming one of the main constitutions of this study.